2015
DOI: 10.1002/joc.4401
|View full text |Cite
|
Sign up to set email alerts
|

Extreme temperature and precipitation events over Italy: assessment of high‐resolution simulations with COSMO‐CLM and future scenarios

Abstract: This study presents a detailed analysis of the present and expected future extreme climate conditions over Italy through the use of some extreme indicators. Climate data for this analysis were provided by the regional climate model COSMO-CLM, using different grid spacing to ascertain the real importance of using higher resolution climate data, especially over such a complex topography as Italy. Four simulations were carried out at spatial resolutions of 0.125 ∘ and 0.0715 ∘ , driven by ERA-Interim Reanalysis a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
54
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 84 publications
(68 citation statements)
references
References 44 publications
(62 reference statements)
8
54
0
Order By: Relevance
“…The simulations have been deeply analysed in Bucchignani et al (2015) and -in terms of extreme events -in Zollo et al (2015a), showing a general good agreement with observed data. Furthermore, as explained in Bucchignani et al (2015), the results of these simulations are consistent, in terms of both mean bias and projections, with those obtained from the EURO-CORDEX ensemble data (Giorgi et al, 2009), which represent the 'state-of-the-art' of regional climate simulations over Europe at 0.11°of horizontal resolution.…”
Section: Climate Simulationssupporting
confidence: 68%
See 1 more Smart Citation
“…The simulations have been deeply analysed in Bucchignani et al (2015) and -in terms of extreme events -in Zollo et al (2015a), showing a general good agreement with observed data. Furthermore, as explained in Bucchignani et al (2015), the results of these simulations are consistent, in terms of both mean bias and projections, with those obtained from the EURO-CORDEX ensemble data (Giorgi et al, 2009), which represent the 'state-of-the-art' of regional climate simulations over Europe at 0.11°of horizontal resolution.…”
Section: Climate Simulationssupporting
confidence: 68%
“…However, the huge computational costs required to perform high-resolution simulations with model ensembles represent a limit, leaving this solution to future works. Indeed, COSMO-CLM results have been proved to be consistent with the 'state-of-the-art' of regional climate simulations (Bucchignani et al, 2015;Zollo et al, 2015a).…”
Section: Discussionsupporting
confidence: 58%
“…The good capabilities of the model in reproducing PDFs observed in the present work, combined with the finding of several literature works (e.g., [33,37]) confirm that, especially in some complex areas, high-resolution simulations could provide good improvements in the data quality. Indeed, there is no ideal resolution appropriate for every geographical area, since it depends on the climate variability of the context considered.…”
Section: Discussionsupporting
confidence: 87%
“…If the comparison was made with lower-resolution data sets, many features of the finer-resolution simulations would have been smoothed out (Vautard et al 2013). Although Kotlarski et al (2014) recommended interpolation to the coarsest-resolution grid, we employed the first approach to provide information for impact studies, as supported by Zollo et al (2015). This method allowed preservation of extreme values and temporal variability (Vautard et al 2013).…”
Section: Observational Data Setsmentioning
confidence: 99%